Reviews. Issue 1 (1st April 2016) - Cohen-Cruz, Jan; Wood, Craig
Applied Theatre Research: Radical Departures by Peter O'Connor and Michael Anderson (2015) Bloomsbury, London ISBN 9 7814 7251 3854 (ebook), US$24.99.Critical Plays: Embodied Research for Social Change, by Anne Harris and Christine Sinclair (2014) Sense, Rotterdam ISBN 9 7894 6209 7537 (pb), 9789462097544 (hb), 9789462097551 (ebook), $36.00 (pb).